The Influence of Dentine on the pH of Calcium Hydroxide, Chlorhexidine Gel, and Experimental Bioactive Glass-Based Root Canal Medicament - Ceci Nunes Carvalho; Laila Gonzales Freire; Alexandre Pinheiro Lima de Carvalho; Evandro Luiz Siqueira; José Bauer; Giovana Cunha Gritti; Juliana Pereira de Souza; Giulio Gavini (The Scientific World Journal)
Objectives. To evaluate the influence of dentine on the pH of different medications in standardized simulated canals. Materials and Methods. Forty resin blocks were divided into groups with and without dentine powder, as follows: 2% chlorhexidine gel; 2% chlorhexidine gel associated with calcium hydroxide PA; calcium hydroxide PA delivered in propylene glycol 600; and NPG delivered in distilled water. The dentine powder was obtained from the root dentine of bovine teeth and added to the medications. The simulated canals were placed in containers with 1.5 mL of deionized water and pH was monitored in multiple intervals, up to 30 days. The mean pH values were calculated and submitted to statistical analysis using paired Student’s t-test and ANOVA complemented by the Tukey test (p<0.05). Results. There was no statistical difference between the groups with and without dentine powder (p>0.05). The pH values of calcium hydroxide were significantly higher than those of NPG in the first 24 hours (p<0.05). After 7 days, both behaved in a similar manner. Conclusion. The addition of dentine powder to the medications evaluated did not alter the pH of the external solution in any of the time points tested.